Efficient synthesis of pyrazolopyridines containing a chromane backbone through domino reaction - Navari, Razieh; Balalaie, Saeed; Mehrparvar, Saber; Darvish, Fatemeh; Rominger, Frank; Hamdan, Fatima; Mirzaie, Sattar (Beilstein journal of organic chemistry, 2019)
Beilstein Journal of Organic Chemistry
Gesehen am 31.10.2019